Tarsal switch using an anterior approach to correct severe ptosis - Meneghim, Roberta Lilian Fernandes de Sousa [UNESP]; Ferraz, Lucieni Barbarini [UNESP]; Galindo-Ferreiro, Alicia; Khandekar, Rajiv; Sanchez-Tocino, Hortensia; Schellini, Silvana [UNESP] (Thieme, 2018)
Background To present the outcomes of the tarsal switch procedure using an anterior approach to correct severe ptosis with poor levator muscle function (< 4 mm) with absent or poor Bell’s phenomenon. Methods This retrospective case series included 11 patients with severe neurogenic or acquired myogenic palpebral ptosis. All patients underwent the tarsal switch procedure through an anterior approach from 2012 to 2015. Margin reflex distance (MRD1 and MRD2) and the palpebral fissure were evaluated preoperatively and postoperatively. Data were compared using the Wilcoxon signed-rank test. P-values < 0.05 were considered to indicate statistical significance. Results Surgery was performed on 18 eyelids (11 patients). The median age at surgery was 57 years (range, 29-86 years). Four patients had unilateral ptosis and seven had bilateral ptosis. Nine patients had myogenic ptosis and two had neurogenic ptosis. Postoperatively, the chin-up position improved in all patients. The MRD1 increased statistically significantly, from 0 mm preoperatively to 1.0 mm postoperatively (P=0.001). The MRD2 decreased statistically significantly, from 4.5 mm preoperatively to 3.0 mm postoperatively (P= 0.001). The palpebral fissure did not change (4.0 mm preoperatively to 4.0 mm postoperatively) (P= 0.13). Conclusions The tarsal switch procedure through an anterior approach is an effective alternative for correcting severe ptosis, especially neurogenic or acquired myogenic ptosis. This procedure can be performed with minimal risk of ocular surface exposure and provides stable outcomes.
Keywords: Blepharoptosis; Transplantation; Transplants